JAMBI PROVINCE PREPARATION FOR THE IMPLEMENTATION OF THE EUROPEAN UNION DEFORESTATION REGULATION - Armando, Fitra; Fitri Harahap, Yulia; Nofriadi, Edo; Humaira, Ghaniyah; Namira Ardinal, Shalma; Ismail, Chintya (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2025)
The European Union Deforestation Regulation (EUDR) is a challenge for all plantation producers. Jambi Province, which is famous for its palm oil and rubber products, finds itself with a new regulation that will bind the terms and conditions for its sales and purchases. This EUDR was originally effective on December 31, 2024. However, its application was delayed until December 31, 2025. The purpose of this study is to see the preparation of Jambi Province in welcoming the EUDR. Using a qualitative research method, open interviews. Interviews were conducted with the Head of the Agriculture Department, and PTPN IV regional 4 and head of the marketing team from the Ministry of Agriculture. The results of the interview showed that currently Jambi Province through the Sustainable Palm Oil Regional Action Plan (RAD KSB) program through BioCF funding and Palm Oil Profit Sharing Funds is trying to carry out ISPO certification for oil palm farmer groups in Jambi Province. However, in the process, this activity was deemed insufficient due to budget constraints which resulted in the certification target being only a few small groups in 2025. Head of the Marketing Working Team made a recommendation to involve third parties in acceleration efforts. So that the limited funds do not need to be used for tagging, enough for data verification with the village government. By adopting the recommended scheme, it is hoped that Jambi Province can be better prepared to face the end of 2025 when EUDR has begun to be implemented.